A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 15 PEKANBARU IN READING COMPREHENSION - Fajar Sumirat; Fakhri Ras; Syafri K ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study is to find out the ability of the first year students of SMAN 15 Pekanbaru in reading comprehension. This research focuses on students’ reading comprehension in terms of finding main ideas, factual information, the meaning of vocabulary, identifying references and finding generic structure, finding social function and finding conclusion,.The data were collected by using reading comprehension test in the format multiple choice. The test contained 25 items. The try out was conducted to check the validity and reliability of the test. Based on the research, it was found out that first: the ability of the second year students in reading comprehension isin the mediocre level with the mean score of 55.6. Second, the students’ mean score in finding the main idea is in mediocre level with the mean score of 55.56, finding the fatual information is in mediocre level with mean score of 48.95, in finding meaning vocabulary is in good level with mean score of 39.95, in finding references is in mediocre level with the mean score of 66.66, in finding social function level with the mean score of 50.87, generic structure in the good level with mean score 63.17, as a conclusion, the highest score obtained by students is in finding generic structure with the mean score of 68.5. It is categorized into good level, and the lowest score that the students got is in finding vocabulary, with the mean score of 3399.9 which categorized into poor level. The results of this study suggest that the students learn more about reading comprehension.Keywords : Study, Ability, Reading Comprehension.